2012
DOI: 10.1258/ar.2011.100252
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient measurements of the pancreas, pancreas carcinoma, and mass-forming focal pancreatitis

Abstract: Background: Mass-forming focal pancreatitis (FP) may mimic pancreatic cancer (PC) on magnetic resonance (MR) imaging, and the preoperative differential diagnosis is often difficult. Recently, the usefulness of diffusion-weighted imaging (DWI) in the diagnosis of pancreatic cancer has been reported in several studies. Purpose: To investigate if apparent diffusion coefficient (ADC) measurements based on diffusion-weighted echo-planar imaging (DW-EPI) may distinguish between normal pancreas parenchyma, mass-formi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 21 publications
5
34
0
Order By: Relevance
“…Thomas et al (Thomas et al, 2012) presented 93% sensitivity and 87% specificity in the detection of AP with b values 0 and 800 sec/mm2, predicted lower ADC values in the AP group than the normal controls. Wiggermann et al (Wiggermann et al, 2012) revealed significant differences for ADC values between pancreatic cancer and normal pancreas, between focal pancreatitis and normal parenchyma which can clearly differentiate the normal pancreatic tissue and abnormal pancreas parenchyma, without any statistical differences between pancreatic cancer and pancreatitis in a series of 64 patients. The consequent obstacle of a significant overlap of ADC values for pancreatic cancer and chronic pancreatitis can be due to fibrotic and focal inflammatory reactions in chronic pancreatitis, causing difficulty in the differentiation of both of these pancreatic lesions (Takeuchi et al, 2008;Wiggermann et al, 2012;Taniguchi et al, 2009).…”
Section: General Knowledge About Current Dwi Techniquementioning
confidence: 99%
See 4 more Smart Citations
“…Thomas et al (Thomas et al, 2012) presented 93% sensitivity and 87% specificity in the detection of AP with b values 0 and 800 sec/mm2, predicted lower ADC values in the AP group than the normal controls. Wiggermann et al (Wiggermann et al, 2012) revealed significant differences for ADC values between pancreatic cancer and normal pancreas, between focal pancreatitis and normal parenchyma which can clearly differentiate the normal pancreatic tissue and abnormal pancreas parenchyma, without any statistical differences between pancreatic cancer and pancreatitis in a series of 64 patients. The consequent obstacle of a significant overlap of ADC values for pancreatic cancer and chronic pancreatitis can be due to fibrotic and focal inflammatory reactions in chronic pancreatitis, causing difficulty in the differentiation of both of these pancreatic lesions (Takeuchi et al, 2008;Wiggermann et al, 2012;Taniguchi et al, 2009).…”
Section: General Knowledge About Current Dwi Techniquementioning
confidence: 99%
“…Wiggermann et al (Wiggermann et al, 2012) revealed significant differences for ADC values between pancreatic cancer and normal pancreas, between focal pancreatitis and normal parenchyma which can clearly differentiate the normal pancreatic tissue and abnormal pancreas parenchyma, without any statistical differences between pancreatic cancer and pancreatitis in a series of 64 patients. The consequent obstacle of a significant overlap of ADC values for pancreatic cancer and chronic pancreatitis can be due to fibrotic and focal inflammatory reactions in chronic pancreatitis, causing difficulty in the differentiation of both of these pancreatic lesions (Takeuchi et al, 2008;Wiggermann et al, 2012;Taniguchi et al, 2009). Head and body of pancreas reveal slightly higher ADC values when compared with the tail, ADC values of pancreatic adenocarcinoma tend to be lower than normal pancreas b factor images can't be totally attributed to the T2-shine-through effect (Wang et al, 2011;Takeuchi et al, 2008;Wiggermann et al, 2012;Inan et al, 2008).…”
Section: General Knowledge About Current Dwi Techniquementioning
confidence: 99%
See 3 more Smart Citations